Efektivitas Model Evaluasi CIPP dalam Program Pendidikan: Kajian Literatur Sistematis - Riawan, I Made Oka; Citariani, Ni Made; Lokasanti, I Ketut (Jurnal Evaluasi Pendidikan, 2025)
This study aims to systematically examine the effectiveness of the CIPP (Context, Input, Process, Product) evaluation model in various educational programs. A Systematic Literature Review (SLR) method was employed to identify, evaluate, and synthesize relevant findings from previous studies. Data were collected from various national and international journal databases, with inclusion criteria covering publications from 2022 to 2025, using keywords such as "educational program evaluation", "CIPP model", and "program effectiveness". The findings indicate that the CIPP model has been consistently applied to evaluate various aspects of educational programs, ranging from planning and implementation to final outcomes. This model has proven effective in providing comprehensive, data-driven insights to support decision-making in educational programs. The study recommends broader application of the CIPP model, particularly in evaluating innovative and digital-based programs.